MANAJEMEN LABA, TRANSFER PRICING, DAN PENGHINDARAN PAJAK SEBELUM DAN PADA MASA PENDEMI COVID-19 - Sartika Wulandari; Rachmawati Meita Oktaviani; Sunarto Sunarto (Politeknik Ganesha Medan, 2023)
The Covid-19 pandemic has caused uncertainty that must be faced by companies, including causing a decrease in revenue which results in a tax burden borne by the company. Tax avoidance is designed to reduce the tax burden, it can be the main agenda of company management, especially when experiencing financial difficulties. This study aims to provide empirical evidence regarding the effect of earnings management and transfer pricing on tax evasion, as well as examine differences in tax evasion before and during the Covid-19 pandemic. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2020 period. By using purposive sampling technique, data were obtained from 62 companies. The results show that earnings management has no effect on tax evasion, and transfer pricing has a significant positive effect on tax evasion. Transfer pricing is carried out on related parties who easily arrange pricing unfairly by raising prices or lowering prices, so that the existence of transfer pricing practices can minimize the tax that must be paid. After conducting a different test with the Wilcoxon Non-Parametric Test, it can be concluded that there is no difference in tax evasion before and during the Covid-19 pandemic. The tax incentives during a pandemic which can be an opportunity for managers to take advantage of greater tax avoidance, but this does not motivate managers to be more aggressive in implementing tax avoidance practices